VisStoryMaker: supporting non-expert analysts in visually exploring datasets and communicating insights with visual annotations and data stories - Braga, Dieinison Jack Freire; Silva, Marisa Carmo da; Lima, Raul de Araújo; Barbosa, Gabriel Diniz Junqueira; Barbosa, Simone Diniz Junqueira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
Due to data production and availability growth, professionals in several disciplines have been facing an increasing need to explore and understand data, obtain insights, and communicate them effectively. Many visualization systems have been developed commercially and within the research community to support non-expert analysts. We can consider at least three challenges these tools aim to face: support the selection of appropriate visualizations and decide on the visual mappings, extract and communicate factual information from the visualizations, and use visualizations in data-rich narratives. In response to these challenges, we developed VisStoryMaker, a visualization tool that supports both exploration and communication about data. To aid users in exploring and understanding data, VisStoryMaker recommends visualizations through system-generated questions and data facts. To support communicating about data, the system recommends visual annotations of data facts and provides a story-building module, allowing analysts to use the generated charts and facts as a blueprint for a data story. We have conducted empirical studies to compare VisStoryMaker's features with existing applications: chart recommendations with Voyager~2, storytelling construction with Flourish, and data facts and chart annotations with Tableau. Our findings indicate that the system-generated questions and data facts supported non-expert analysts in exploratory analysis. They perceived visual data facts annotations as useful and supported them in raising hypotheses about the data, understanding data, and leading to insights, thus enhancing data analysis. Participants perceived the visual annotations and StoryMaker as helpful in organizing the system-generated pieces of information and incorporating them into comprehensive narratives and presentations.